“Small Talk” in the Innate Immune System via RNA-Containing Extracellular Vesicles - van der Grein, Susanne G.; Nolte-’t Hoen, Esther N. M. (Frontiers in Immunology, 2014)
A newly uncovered means of communication between cells involves intercellular transfer of nano-sized Extracellular Vesicles (EV), composed of lipids, proteins, and genetic material. EV released by cells of the immune system can play a regulatory role in the induction and suppression of immune responses. These functions may be mediated not only by the bioactive lipids and proteins present in EV, but also by EV-associated RNAs. The RNA in EV mainly consists of miRNAs and a large range of other small non-coding RNA species. Since many of these small RNAs have the potential to regulate gene expression, intercellular transfer of these RNAs via EV may cause long-term changes in the function of EV-targeted cells. Several types of innate immune cells release EV that affect innate immune responses and other (patho)physiological processes. Additionally, the innate immune system is influenced by EV released by non-immune cells and EV found in body fluids. In this review we focus on how EV-associated RNAs contribute to these immune regulatory processes.